re- Rekonstruksi Model Pemberdayaan Pengungsi Syiah Sampang di Sidoarjo - Imam Bonjol Juhari (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2019)
Abstract: This article builds a community empowerment model based on theoretical foundations and empirical data on the refugees from the Syiah Sampang community in Rusun Puspa Agro Jemundo Sidoarjo. The focus of the refugee empowerment construction consists of several elements so that the empowerment program becomes optimal, namely; first, there is a synergy between the bureaucratic apparatus, related agencies, NGOs, and active participation of target groups in planning, decision making, and program evaluation. Second, effective communication and cooperation between bureaucratic officials, related agencies and NGOs, in guiding program implementation. Third, the element of effective monitoring from the bureaucracy, related agencies, NGOs by involving the participation of the program target group. The empowerment of Syiah Sampang refugees, which has been carried out so far, does not pay attention to these elements so that the process and final goal of the empowerment program to improve the welfare of refugees are not optimal.